1996
DOI: 10.1007/bf02523448
|View full text |Cite
|
Sign up to set email alerts
|

Carboxymethyl inulin: A new inhibitor for calcium carbonate precipitation

Abstract: A new polysaccharide‐based polycarboxylate, carboxymethyl inulin (CMI), was synthesized recently. The influence of small amounts (0.1–200 ppm) of this material on the crystallization of calcium carbonate, an important scale‐forming salt, is studied. The effects of CMI are compared to those of a commercial inhibitor (a copolymer of acrylate and maleate) and of other carboxymethylated saccharides. It is shown that CMI is a good calcium carbonate precipitation inhibitor. CMI influences the spontaneous precipitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(32 citation statements)
references
References 17 publications
0
31
0
Order By: Relevance
“…Attachment of the carboxymethyl moieties occurs predominantly at the C-2 and C-6 glucose positions with a preference for C-6 vs. C-2 (Heinze & Pfeiffer, 1999). Its water solubility, rheological properties, non-toxicity, and polyelectrolyte nature favor its use in many diverse applications, such as food additives (Parvar, Tehrani, Razavi, & Koocheki, 2013), pharmaceutics (Chukwumezie, Wojcik, Malak, & Adeyeye, 2002), bone regeneration (Jiang, Li, Zhang, & Wang, 2009), adhesives (Kawamoto, 2003), textiles (Krizova & Wiener, 2013), pesticides (Nisar, Kumar, Shakil, Pankaj, & Parmar, 2009), detergents (Verraest, Peters, van Bekkum, & van Rosmalen, 1996), paper (Li, Liu, Xu, & Xu, 2010;Watanabe, Gondo, & Kitao, 2004), and ceramic binders (Khosrowshahi & Salem, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Attachment of the carboxymethyl moieties occurs predominantly at the C-2 and C-6 glucose positions with a preference for C-6 vs. C-2 (Heinze & Pfeiffer, 1999). Its water solubility, rheological properties, non-toxicity, and polyelectrolyte nature favor its use in many diverse applications, such as food additives (Parvar, Tehrani, Razavi, & Koocheki, 2013), pharmaceutics (Chukwumezie, Wojcik, Malak, & Adeyeye, 2002), bone regeneration (Jiang, Li, Zhang, & Wang, 2009), adhesives (Kawamoto, 2003), textiles (Krizova & Wiener, 2013), pesticides (Nisar, Kumar, Shakil, Pankaj, & Parmar, 2009), detergents (Verraest, Peters, van Bekkum, & van Rosmalen, 1996), paper (Li, Liu, Xu, & Xu, 2010;Watanabe, Gondo, & Kitao, 2004), and ceramic binders (Khosrowshahi & Salem, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Backfolk et al [46] and Verraest et al [47] have shown that CMC can form complexes with Ca 2+ , and we thus expect CMC to control the nucleation and crystal growth of CaCO 3 in a similar fashion as the polyacrylates. Previous work has shown that CMC is not able to replace a preadsorbed polyacrylate from the surface of the CaCO 3 particles [46].…”
Section: Caco 3 Colloidal Filmsmentioning
confidence: 94%
“…Modifications of inulin may expand the amount and type of technological applications because most of these compounds are readily biodegradable. For example, in the chemical industry, modified inulin by different chemistry processes is used as chelating agent and antifouling in pipes, containers, reaction chambers, and separation equipment, among others, or converted into plastic films as a proposed alternative for the substitution of petroleum polymers (Grandther et al 2005;Kasapis 2006;Verraest et al 1996).…”
Section: Technological Applications Of Inulinmentioning
confidence: 99%